Spinal Pedicle Morphometry using Multidetector CT—An experience from the Indian Subcontinent - Sahu, Samaresh; Yadav, Ravinder; Sudhan, Manoharan D.; Rao, Akhilesk; Mohimen, Aneesh (Indian Journal of Neurosurgery, 2021)
Introduction For safe pedicle screws placement, knowledge of pedicle morphometry is essential, because an inconsistency between pedicle width and the screw diameter may lead to severe complications like nerve, vessel or visceral injuries.Objectives To study the spinal pedicle width and height of lumbar spine, using multidetector CT (MDCT), among the Indian population. To study the spinal pedicle angulation of lumbar spine, using MDCT, among the Indian population.Method The study was conducted at a tertiary care multispecialty hospital. In the present study, a total of 321 patients were included, who underwent MDCT scan without contrast at our institution, over a period of 2 years, from May 2017 to May 2019. The study population (n = 321) was divided into different subgroups on the basis of the age. The data was taken from the workstation. Comparison was made separately between each subgroup.Results In our subset of population, the 10 to 90 years age group, pedicle dimensions are as follow: The pedicle diameter from L1 to L5 is 4.46 to 11.92 mm. The pedicle height from L1 to L5 is 7.38 to 11.01 mm. The pedicle axial angulation from L1 to L5 is 22.27 to 36.08 degree. The pedicle lateral angulation from L1 to L5 is 16.12 to 22.47 degree.Conclusion Knowledge of the pedicle morphometry (pedicle width, height and angulation) of lumbar spine will help the neurosurgeons standardize the size of pedicle screws which is required for spinal fixation surgery at various lumbar vertebra levels.
Keywords: spinal pedicle; multidetector CT scan; morphometry; lumbar spine